HUBUNGAN DUKUNGAN KELUARGA DENGAN PROSES RUJUKAN DINI BERENCANA DI WILAYAH KABUPATEN LUMAJANG - Kusuma, Greasia Adi; Alfitri, Rosyidah; Indriati, Ina (NHM PRESS, 2024)
According to the World Health Organization (WHO) report, globally around 830 women die every day due to complications during pregnancy and childbirth, with a maternal mortality rate of 216 per 100,000 live births, where 99% of maternal deaths are caused by problems related to pregnancy and childbirth. , One of the factors causing death is delays in getting fast and appropriate health services. Early referral is an important step in dealing with high-risk patients (Listyorini, 2019). Support from the family has an important role in increasing a person's self-confidence, especially for pregnant women who are at high risk in making decisions (Harahap, 2021). The research aims to determine the relationship between family support and the early planning referral process in the Lumajang Regency area. This research is a quantitative research with a cross sectional approach. The population and sample of this research were 18 pregnant women in the Penanggal Community Health Center, Lumajang Regency, the sample was taken using accidental sampling technique. Data was collected using a questionnaire and the data was analyzed using the contingency coefficient test. The results of the research illustrate that 8 respondents had sufficient family support, 5 respondents each had good and poor support. Meanwhile, there were 9 respondents who experienced early planning referrals, the same as respondents who did not experience early planning referrals. The statistical results of the contingency coefficient test obtained p-value = 0.007 < 0.05, which means that there is a relationship between family support and the planned early referral process in the Lumajang Regency area. Because family support is so important in carrying out the early referral planning process, providing health services requires strong supervision and education for family involvement in every medical service that will be provided.